Arthroscopic Treatment of Anterior Shoulder Instability Using Suture Anchors With Pre-Tied Knots in the Beach Chair Position - Cameron G. Thomson MD; Ramsey S. Sabbagh BS; Nihar S. Shah MD; Jorge H. Figueras BS; Brian M. Grawe MD (SAGE Publishing, 2022)
Background: Arthroscopic Bankart repair is routinely performed for treatment of anterior shoulder instability. Although an overall successful procedure, arthroscopic free-hand knot tying can be challenging and inconsistent, even for experienced surgeons. Knotless anchors, on the other hand, pose challenges in developing consistent good loop security prior to implantation, and, in the absence of a secure loop tissue tension on the glenoid face, might be inadequate. As an alternative, suture anchors with pre-tied knots offer the strength and security of knots without the need to perform complex and unreliable free-handed ties. Furthermore, loop security is consistent, reliable, and effective with each anchor. Indications: Patients with anterior labral tears and minimal bone loss are candidates for arthroscopic Bankart repair. The goal of surgery is to restore a robust tissue profile and statically keep the humeral head well-seated within the glenohumeral joint space. Technique Description: We demonstrate how to perform Bankart repair using suture anchors with pre-tied knots. The torn labrum is first mobilized and elevated, and suture anchors are placed along the glenoid rim from inferior to superior, treating the torn tissue as "rungs of a ladder." The pre-tied sliding knot secures the restored labrum, along with glenohumeral ligaments and capsule, as necessary, using only a limited number of incrementally tensioned half hitch knots. Results: Of the 30 patients treated for anterior shoulder instability using this technique, the majority met the minimal clinically important improvement in the American Shoulder and Elbow Surgeons Shoulder Score, Western Ontario Shoulder Instability Index, and Marx activity scale by 2 years. Two patients reported experiencing subsequent minor subluxation events that improved following short courses of physical therapy, and no patients sustained subsequent frank dislocations. Discussion/Conclusion: Using suture anchors with pre-tied knots for arthroscopic Bankart repair allows for fast, easy, and consistently dependable reconstruction of the labrum and leads to reliable clinical outcomes.